Instructions Qualitative Assessment of Students’ Spiritual and Social Attitudes: A Holistic Approach in Islamic Education - Habib Zainuri (Fakultas Agama Islam Universitas Kutai Kartanegara Tenggarong, 2025)
Assessing students’ spiritual and social attitudes remains challenging because these dimensions are complex, contextual, and not easily captured through numerical measures. This study aims to examine how qualitative assessment can provide a more holistic understanding of students’ spiritual and social attitudes in Islamic education. The study employs a qualitative library research method by analyzing scholarly books, journal articles, and relevant academic works on qualitative evaluation. The findings indicate that qualitative assessment through approaches such as reflective interpretation, narrative analysis, and context-sensitive evaluation offers richer and more comprehensive insights into students’ values, empathy, and social behavior. It enables educators to generate meaningful feedback that supports character development. However, issues of subjectivity and generalizability remain concerns. This study concludes that qualitative assessment is a valuable holistic approach for understanding and fostering students’ spiritual and social development in educational settings.